The secret language of girls - Dowell, Frances O'Roark. (New York : Atheneum Books for Young Readers, 2004)
Marylin and Kate have been friends since nursery school, but when Marylin becomes a middle school cheerleader and Kate begins to develop other interests, their relationship is put to the test.
Accelerated Reader AR
Keywords: Best friends -- Fiction; Friendship -- Fiction; Schools -- Fiction